Humor and Wisdom: A Critical Analysis of Binary Oppositionsin Tenas Effendy’s Pantun Kelakar - Aris, Qori Islami; Syam, Essy (Universitas Negeri Semarang, 2024)
This study examines the nuanced application of binary oppositions in Tenas Effendy's